Physical and Chemical Characteristics of Chosen Genotype of Robusta Coffee from Curahpoh Village Bondowoso East Java - Meliala, Susan Barbara Patricia Sembiring; Setiyono, Setiyono; Savitri, Dyah Ayu; Arum, Ayu Puspita; Hidayah, Satria Nurul Hidayah; Noviana, Sulfi (Newinera Publisher, 2024)
The identity of coffee is significant for consumers mostly in relation to the characteristics of the end result product taste and quality. Robusta coffee varieties are widely grown by farmers in Bondowoso Regency in east Java, Indonesia using planting materials of unknown origin. The objective of this work was to identify the physical and chemical occurrence of Robusta cherries harvested from seven chosen genotypes grown in Curahpoh Village, Bondowoso. Samples of Robusta coffee cherries of seven selected genotype plants were harvested from Curahpoh Village, Bondowoso at three levels of maturity. Some physical and chemical factors were assessed as follows: sphericity, bean density, weight per bean, moisture content, total dissolved solids, to elicit differences in the genotypes. Analyzing the results obtained, the authors pointed to rather serious differences in these characteristics between various genotypes. The sphericity of fresh coffee fruits ranged from 0.82 to 0.93, with average density values between 1.00 and 1.11 g/cm³. The moisture content of green beans varied widely from 4.46% to 22.79%, while total dissolved solids ranged from 2.67% to 5.27%. These studies suggest the possibilities of genotypes selection in order to produce a superior genotype that would improve the quality as well as the marketability of Bondowoso Robusta coffee. These data contribute to the enhancement of the current agricultural practices, and the proposal of new varieties of coffee adapted to the specifics of their environment.